The Hippo tumor-suppressor pathway regulates apical-domain size in parallel to tissue growth - Hamaratoglu, Fisun (Company of Biologists, 2009)
The Hippo tumor-suppressor pathway controls tissue growth in Drosophila and mammals by regulating cell proliferation and apoptosis. The Hippo pathway includes the Fat cadherin, a transmembrane protein, which acts upstream of several other components that form a kinase cascade that culminates in the regulation of gene expression through the transcriptional coactivator Yorkie (Yki). Our previous work in Drosophila indicated that Merlin (Mer) and Expanded (Ex) are members of the Hippo pathway and act upstream of the Hippo kinase. In contrast to this model, it was suggested that Mer and Ex primarily regulate membrane dynamics and receptor trafficking, thereby affecting Hippo pathway activity only indirectly. Here, we examined the effects of Mer, Ex and the Hippo pathway on the size of the apical membrane and on apical-basal polarity complexes. We found that mer;ex double mutant imaginal disc cells have significantly increased levels of apical membrane determinants, such as Crb, aPKC and Patj. These phenotypes were shared with mutations in other Hippo pathway components and required Yki, indicating that Mer and Ex signal through the Hippo pathway. Interestingly, however, whereas Crb was required for the accumulation of other apical proteins and for the expansion of the apical domain observed in Hippo pathway mutants, its elimination did not significantly reverse the overgrowth phenotype of warts mutant cells. Therefore, Hippo signaling regulates cell polarity complexes in addition to and independently of its growth control function in imaginal disc cells.